Stakeholder model application in tourism development in Cat Tien, Lam Dong - BUI DUC SINH; VO THI NGA; VO TRAN HAI LINH; NGUYEN HOANG TUAN (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: The purpose of this research was to examine the potential of Cat Tien as a tourist destination by analyzing the advantages and disadvantages of the industry, with the ultimate goal of constructing a tourist industry that is respectful of Cat Tien’s cultural heritage and that contributes to the city’s economic growth.Method: Quantitative methods were used for data collection and presentation, with a survey of local residents processed through SPSS for statistical analysis and Likert scales for measuring local residents’ awareness and expectations.Findings: Therefore, it is clear that there is no connection between the dependent and independent variables. These results suggest that respondents of all backgrounds and familiarity with Cat Tien’s history and culture strongly favor the industry’s expansion. Those who work in the tourism industry are also more likely to believe that the industry plays a significant role in the economy.Implications/Novel Contribution: This study has uncovered some concerns, particularly from local residents who participated in the research, that tourism development in this area has not improved their quality of life, even though on a macro level, tourism has a strong link to other sectors. As a result, society’s stakeholders won’t be able to make effective contributions, which will slow the expansion of the local economy in the eyes of the general public